Простий метод визначення кислотного числа рослинних олій та олеохімічних продуктів - Zubenko, S.O. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2021)
Acid value is one of the key technical characteristic of vegetable oils and oleochemicals, obtaining on its basis. The existing standard methods of acid value measurement are relatively complicated and have some disadvantages. There are including utilization of the significant amounts of solvents, throwing out as wastes, and necessity in special equipment for determination. Also, a special issue is visual indication of the equivalence point of indicator transfer from acid to alkali form for intensive colored oils’ samples. Visual indication of the color transfer of phenol-phthalein as indicator (from colorless to pink) is quite difficult. The color transfer of thymolphthalein (from yellow to green) in such condition is not determined. Using of alkali blue 6B is complicated by the necessity of use ethanol and aromatic compounds mixture. In current work the rapid and simple method of acid value determination was proposed. It consists in alkaliacid titration of the sample by sodium butoxide solution in n-butanol with bromothymol blue, n-butanol is also using as solvent. The method was tested on 3 series of the mixtures of the refined sunflower oil and free fatty acids (distilled fatty acids of sunflower and rapeseed oils and chemical grade oleic acid). The fatty acid content in tested mixtures was in range 1-50 % wt. Some disadvantages of traditional methods, such as the necessity of mixed solvents’ and relatively complicated laboratory equipment use, titration in a hot state, effect of temperature changes in the laboratory and difficulties with visual indication of color transfer, were overcame. Proposed method requires only the simplest laboratory glassware (conic flasks, non-calibrated pipettes, hermetically sealed glass vessels for titrant) and technical laboratory scales (weighting accuracy ±0.01 g). The method allows to determine the acid value in wide range of samples, including the samples with intense coloration. The relatively high accuracy of acid value determination was shown. The method sensitivity is 0.02-0.10 mg KOH/g. The time for analyze is enough short (about 5-15 minutes).